Contribution to the knowledge of Dialeurodes (Gigaleurodes) Quaintance & Baker (Hemiptera: Aleyrodidae), with description of a new species from China - Wang, Ji-Rui; Du, Yu-Zhou; Xu, Zhi-Hong; Zhou, Guo-Xin (Zootaxa, 2021)
A new whitefly species, Dialeurodes (Gigaleurodes) parakmeriae Wang sp. nov., collected on Parakmeria sp. (Magnoliales: Magnoliaceae) in Shuangxikou (Zhejiang, China) is described using morphology, line illustrations, photographs and scanning electron microscope (SEM) images. In addition, Dialeurodes (Gigaleurodes) maxima Quaintance & Baker, is reported as new to the fauna of China. An identification key to Chinese Dialeurodes (Gigaleurodes) species is provided. The holotype is deposited in the Insect Collection of Zhejiang Agriculture & Forestry University (ZAFU).